Profanity and Characterization: A Study of Translation Strategies and Their Effects on The Catcher in the Rye - Azura, Fachrina; Dewi, Haru Deliana; Hidayat, Rahayu Surtiati (Journal of Language and Literature, 2019)
This paper investigates the translation strategies used in translating profanity in the novel The Catcher in the Rye and their effects on the narrator’s characterization. The purpose is to see the effects that certain translation strategies have on characterization, an important literary element. This paper will focus on Chapter 25, the penultimate chapter where the climax takes place. This paper uses statistics to examine the number of translation strategies used and the qualitative-descriptive method to examine the effects on the narrator’s characterization. The strategies will be classified based on Baker’s (2018) proposed strategies, while Nida’s (2012) argument regarding the importance of characterization will be the framework for evaluating the characterization. This paper finds that the Indonesian translator overwhelmingly used the strategies of softening and omission. This results in a significantly different characterization of the narrator, in which he becomes less irreverent and more conscious of social norms.